2008
DOI: 10.1080/03009740802055984
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia in rheumatoid arthritis is associated with inflammatory activity, physical disability, and low bioavailable insulin‐like growth factor

Abstract: A large proportion of RA inpatients, mainly women, had rheumatoid cachexia. The muscle wasting was explained by inflammatory activity and physical disability as well as low bioavailable IGF-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
5
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 49 publications
7
107
5
7
Order By: Relevance
“…Low plasma levels of IGF-1 were found in RA patients [35,36] and elevated IGF binding-proteins further decreased the bioavailability of IGF-1 in RA patients [37]. Dhaunsi et al also showed an association between IGF-1 gene polymorphism and the development of RA [38].…”
Section: Discussionmentioning
confidence: 99%
“…Low plasma levels of IGF-1 were found in RA patients [35,36] and elevated IGF binding-proteins further decreased the bioavailability of IGF-1 in RA patients [37]. Dhaunsi et al also showed an association between IGF-1 gene polymorphism and the development of RA [38].…”
Section: Discussionmentioning
confidence: 99%
“…The consequence is chronic erosion of BCM resulting in a cachectic state. Rheumatoid cachexia is associated with low bioavailability of insulin-like growth factor [13] but, differently from sarcopenia of aging, does not depend on reduced testosterone or growth hormone production [14].…”
Section: Body Composition In Rheumatoid Arthritismentioning
confidence: 99%
“…cachexia that was significantly associated with serum C-reactive protein (CRP) levels and disease activity [13].…”
Section: Body Composition In Rheumatoid Arthritismentioning
confidence: 99%
“…Muscle wasting is a common feature of RA but low BMI is uncommon as the fat mass is preserved or even increased (Summers et al, 2008). Hence, RA patients may present with either the classic low BMI cachexia (1-13% of RA population) (Munro & Capell, 1997) or more frequently, the rheumatoid cachexia (10-20% of RA with controlled disease and 38% of patients with active RA) (Engvall et al, 2008, Metsios et al, 2009). …”
Section: Introduction To Inflammatory Diseasementioning
confidence: 99%